Visual Marketing and its Impact on Consumer Buying Behavior in Clothing Stores - Al- Alsaggaf , Dalia Mohammed Abdullah; Basaffar, Amaal Abdelqader (Advances in Social Sciences Research Journal, 2022)
Visual marketing is concerned with the way products are visually communicated to the consumer. Nowadays, the owners of retail establishments apply visual marketing strategies in their practices in a larger scale and in an innovative way, where they use multiple technologies in order to present the product and make significant investment in the store environment. The problem of the study emerged through the researcher’s review of previous studies on the subject of the study, which indicated to the effect of visual marketing strategies in retail clothing stores on the purchasing behavior of the consumer. The research aims to study visual marketing and its impact on consumer purchasing behavior in the city of Jeddah using the SOR theory to identify the degree of impact of these strategies using the SOR theory model. The research followed the descriptive analytical approach by conducting the study on a sample of 77 consumers in Jeddah, Saudi Arabia. The questionnaire was used as a tool for the study. The results showed that the application of visual marketing strategies significantly affects the change in purchasing behavior of consumers in the city of Jeddah, and that there was a positive statistically significant relationship between purchasing behavior and motivation, mental image, and feelings of happiness. The results also showed a correlation between (stimulus, mental image, and feelings of happiness) and purchasing behavior. The coefficient of determination indicates that the variables (stimulus, mental image, and feelings of happiness) represent 58.3% of the variance in purchasing behavior.